Tissue culture of ornamental cacti (Scientia Agricola, 2015)
Cacti species are plants that are well adapted to growing in arid and semiarid regions where the main problem is water availability. Cacti have developed a series of adaptations to cope with water scarcity, such as reduced leaf surface via morphological modifications including spines, cereous cuticles, extended root systems and stem tissue modifications to increase water storage, and crassulacean acid metabolism to reduce transpiration and water loss. Furthermore, seeds of these plants very often exhibit dormancy, a phenomenon that helps to prevent germination when the availability of water is reduced. In general, cactus species exhibit a low growth rate that makes their rapid propagation difficult. Cacti are much appreciated as ornamental plants due to their great variety and diversity of forms and their beautiful short-life flowers; however, due to difficulties in propagating them rapidly to meet market demand, they are very often over-collected in their natural habitats, which leads to numerous species being threatened, endangered or becoming extinct. Therefore, plant tissue culture techniques may facilitate their propagation over a shorter time period than conventional techniques used for commercial purposes; or may help to recover populations of endangered or threatened species for their re-introduction in the wild; or may also be of value to the preservation and conservation of the genetic resources of this important family. Herein we present the state-of-the-art of tissue culture techniques used for ornamental cacti and selected suggestions for solving a number of the problems faced by members of the Cactaceae family.